PENERAPAN OTAGO EXERCISE DALAM MENGURANGI INSTABILITY DENGAN STROKE DI PANTI WERDHA TRUE LOVE - flin Elianora Betaria Pasaribu; Savitri Gemini (Ensiklopedia of Journal, 2026)
Abstract: Elderly individuals with non-hemorrhagic stroke face high risks of balance disturbances and falls due to motor and cognitive decline. The Otago Exercise Program, a structured regimen to strengthen lower limb muscles and improve balance, has proven effective in reducing fall risk among older adults. This study aims to implement the program to reduce instability, an elderly patient with non-hemorrhagic stroke at the True Love Nursing Home. Using a case study approach within the nursing care process framework, physical examination and revealed weakness and stiffness in the left extremities, with muscle strength scores of 3/3/4/4. The intervention emphasized mobility improvement through six days of Otago Exercise. Interventions followed the plan with goals, contributing to gerontological nursing knowledge. Keywords: Elderly; Non-Hemorrhagic; Otago Exercise.